School-parents relationships: a bibliometric study on 40 years of scientific publications. - Castelli, Stefano; Pepe, Alessandro (International Journal about Parents in Education, 2023)
The present paper explores the amount of research activity estimated through the growth of scientific literature in the field of parents’ participation in their childrens’ schooling: it is a so-called bibliometric analysis. Assessing the “size of science” is a complex task, but bibliometric techniques have been shown to be useful in the development of scientific research activity to address emerging concerns such as the rate of development of a certain discipline and of some specific areas of scientific interest (Katz & Hicks, 1997).Data for analysis were collected from several relevant queries restricted to articles accessible through Cambridge Scientific Abstract (C.S.A.) on-line research platform. Nearly 11,000 bibliographic records were retrieved, with publication dates ranging from 1966 to 2005.In this study researchers attempted to answer two main research questions: which is the rate of literature growth in the field of parent participation (and the expected rate for the forthcoming years)? Which are the different patterns of literature production through different research fields (Pedagogy,Psychology, Sociology, etc.)?Our results reveal a strong growth rate in the number of articles published, and rather significant differences in the various disciplines taken into consideration.